PO 18220 - Talocalcaneal tibio arthrodesis with percutaneous retrograde intramedullary nail: case report - de Schoucair Jambeiro, Jorge Eduardo; Cordeiro Neto, Tavares; Delmonte Moreira, Fernando; de Oliveira, José Augusto; Fernande Leão, Felipe (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Primary osteoarthritis, post-traumatic lesions, Charcot arthropathy and rheumatoid arthritis are some of the causes of ankle and hind foot osteoarthritis that result in pain and sometimes functional limitations in patients affected by such pathology. The therapeutic options vary from conservative treatment (painkillers, bracing and nonsteroidal anti-inflammatory drugs) and surgical treatment. The objective of this present study is to report three cases of patients with ankle osteoarthritis who had undergone minimally invasive surgery (MIS) for tibio-talocalcaneal arthrodesis with an intramedullary nail, with the use of a retrograde blocked intramedullary nail and screws as fixation. Methods: Clinical and radiographic evaluations were conducted of three cases treated using this technique at our institution in 2017, who were allowed full weight bearing postoperatively The AOFAS questionnaire and radiographic evaluation were employed in two orthogonal incidences of the ankle, evaluated after one year postoperatively. Results: We obtained AOFAS scores between 68 and 86 after one year postoperatively with this study technique, and the radiographic consolidation index was observed in 100% of cases (between 6 and 12 weeks) postoperatively. There were no complications. Conclusion: We obtained good results with minimally invasive surgery (MIS) for tibio-talocalcaneal arthrodesis, with satisfactory consolidation presenting no complications. However, there are an insufficient number of studies in the literature demonstrating superiority of the percutaneous tibio-talocalcaneal arthrodesis technique over the open technique. We believe that the percutaneous technique is a recent method fir study that may be added to the therapeutic arsenal.